THE EFFECT OF CONSUMPTION AND THE LABOUR FORCE PARTICIPATION RATE (LFPR) ON ECONOMIC GROWTH IN NORTH SUMATERA PROVINCE - Indra Maipita (Quantitative Economics Journal, 2020)
North Sumatera Provincial Government in implementing regional autonomy and fiscal decentralization policies has tried to implement it based on the needs of each district/city so that a prosperous society is created. The prosperity achieved is not only reflected in high economic growth but is also supported by the fulfillment of realizable consumption needs and the abundant availability of reliable human resources. This study discusses the effect of two variables contained in fiscal decentralization, the level of public consumption and labor absorption on economic growth in North Sumatra. The method used by researchers is regression using panel data (pooled data) or called the panel data regression model. The estimation results show the regression coefficient of the CONS variable is -0.185883. This means that with each increase in CONS by 1 percent, economic growth will decrease by 0.18 percent and vice versa. The effect of the CONS variable on EG is negative and significant at the 95 percent confidence level and the estimation results show the regression coefficient of the Labour Force Participation Rate (LFPR) variable of 0.442641. This means that for each increase in LFPR by 1 percent, economic growth will increase by 0.44 percent and vice versa. The effect of the LFPR variable on PE is significant at the 95 percent confidence level.